The Rhizome of Lokiarchaeota Illustrates the Mosaicity of Archaeal Genomes. (27th September 2017) - Levasseur, Anthony; Merhej, Vicky; Baptiste, Emeline; Sharma, Vikas; Pontarotti, Pierre; Raoult, Didier
Abstract: Genome remodeling and exchange of sequences are widespread in the prokaryotic world and mosaic genomes challenge the classification of prokaryotes, which cannot be properly achieved in terms of a single gene or group of genes. Here, we studied individually the gene collection of the archaic microorganism Lokiarchaeum sp., suggested as an archaeal host close to the emergence of the eukaryotes . The network or rhizome of all Lokiarchaeum sp. genes revealed that the genomic repertoire is mainly composed of genes from archaeal (∼36%) and bacterial origin (∼28%), distantly followed by components of eukaryotic origin (∼2%). Thirty-three percent of genes were unique to this species (ORFans). The mosaicity of archaea was also supported by studying Methanomassiliicoccus luminyensis, an archaea from the gut, in which 67% of the genomic repertoire arised from archaea and 22% from bacteria. Our results illustrate the intricate evolutionary relationships of the archaeal genome repertoire and highlight the rhizome-like processes of evolution in archaea, their mosaicity, and chimeric origin composed of different domains of life, questioning the reality of a tree of life.